Profiling performance in L1 and L2 observed in Greek–English bilingual aphasia using the bilingual aphasia test: a case study from Cyprus - Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2011)
The Greek and the English versions of the Bilingual Aphasia Test (BAT) were used to assess the linguistic abilities of a premorbidly highly proficient late bilingual female after a haemorrhagic cerebrovascular accident involving the left temporo-parietal lobe. The BAT was administered in the two languages on separate occasions by the first author, a bilingual English–Greek speech pathologist. The results revealed a non-parallel recovery in the two languages. This information will be used not only to guide clinical intervention for the patient but also to provide the first report on the manifestations of aphasia in Greek. Moreover, the use of the (Standard Modern) Greek version of the BAT to investigate Greek Cypriot aphasics has implications for the use of the BAT on underspecified languages or dialects. Such studies may help with the development of assessment measures and therapy strategies that focus on specific characteristics of one or multiple languages.
Keywords: Cypriot Greek; Diglossia/bidialectism; Language assessment; Recovery patterns; Underspecified/understudied languages; Multilingualism; Aphasia